Optimal Convex Combination Bounds of Arithmetic and Second Seiffert Means for Neuman-S´andor Mean - Hongyan, Ma; Chunrong, Liu (IJRDO -JOURNAL OF MATHEMATICS, 2016)
In this paper, we present the least value α and the greatest value β such that the double inequality αA(a, b) + (1 − α)T(a, b) < M(a, b) < βA(a, b) + (1 − β)T(a, b) hold for all a, b > 0 with a 6= b, where A(a, b), M(a, b) and T(a, b) are the arithmetic, NeumanS´andor and second Seiffert means of a and b, respectively.